Binding properties of coumarin phthalonitrile derivatives in methanol - Naouali, Olfa; Mellah, Besma; Medyouni, Rawdha; Hamdi, Naceur; Baklouti, Lassaad (European Journal of Chemistry, 2015)
The complexation properties of coumarin phthalonitrile derivatives 1-3, towards some transition, heavy and lanthanide metal cations have been investigated in methanol by means of UV spectrophotometry and conductivity experiments. The stoichiometries of the complexes formed and their stability constants were resolved by digital processing of data. A binuclear M2L (M = Metal, L = Ligand) species were formed and the profiles of affinity of ligands 1-3 towards transition metal cations illustrate their selectivity towards Cu2+.